ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN USAHA KOPERASI KREDIT (CU) BANURI HARAPAN KITA BATANG TARANG KABUPATEN SANGGAU - Kurnia Kurnia; Aminuyati Aminuyati; Sri Buwono (Universitas Tanjungpura, 2022)
This study aims to analyze the SWOT in CU BanuriHarapanKita Batang Tarang Kabupaten Sanggau.Theresearch method used is descriptive with a qualitativeapproach. The data sources in this study were oneadministrator and nine members of CU Banuri HarapanKita Batang Tarang as respondents for interviews. Datacollection was obtained through interview and thedocuments obtained were then analyzed through datareduction, data presentation, and verification/drawingconclusions then checking the validity of the data usingtriangulation techniques. Researchers conducted twointerviews. The reseach show that the strength of CU hasthree factors, namely capital capital growth, determinationof education level and managerial ability and there are fivestrategies to maximize strength. Weaknesses factors are theunvailability of ATM machines and infrastructure and thereis a strategy to minimize weaknesses. CU Banuri HarapanKita have several opportunities, namely governmentregulations that support credit cooperative businesses,technology, the majority of population are farmers, youngpeople who have the potential to enter Cuand there arethree strategies made to take advantage of theseopportunities. The threat of CU Banuri Harapan Kita thereare two factors, namely competition and Covid19 Pandemicand there are three strategies made to minimaze threats.